Uptake in incidental focus-on-form episodes concerning formulaic language in advanced adult EFL classes. (March 2020) - Gholami, Leila; Gholami, Javad
An extensive number of studies have examined the effectiveness of incidental focus on form (FonF) measured through uptake in primarily communicative activities and established an association between learners' uptake of linguistic features and their subsequent second language development. In this strand of research, the analysis of linguistic forms has been constrained to grammar, vocabulary, pronunciation, and spelling. However, as self-contained units of meaning, formulaic sequences (FSs), comprising collocations, lexical bundles, idioms, compounds, etc., have not yet been the object of FonF research. Inspired by the fact that a substantial proportion of natural discourse consists of FSs, the present study investigated the degree to which incidental focus-on-form episodes (FFEs) with formulaic vis-à-vis other linguistic foci occur, and the extent to which they result in (successful) uptake in English as a foreign language (EFL) classes. The data consisted of 36 hours of audio-recorded communicative classroom interactions from three advanced EFL classes. The findings revealed that, though not as frequently as other linguistic elements, learners and teachers regularly draw their attention to FSs. FFEs with formulaic focus, in general, and collocations, in particular, led to more uptake than those with other linguistic foci. Finally, among types of incidental FonF, the highest rate of (successful) uptake was observed in student-initiated FFEs with formulaic focus.